Legal protection of the rights and obligations of the parties in the settlement of construction service contract disputes through Abitrase - Safnul, Dody (Legalpreneur Journal, 2023)
AbstractBusiness activities rife in Indonesia, one of which is the construction services business. The implementation of the construction services business is made by the parties with aconstruction services contract. In the implementation of construction service contracts,sometimes there are construction service disputes between the parties, both providers andusers of construction services, which are decided through arbitration, but there are stillmany arbitration awards that are not in accordance with the principles of Justice, proprietyand certainty so that the arbitration award is applied for cancellation of the decision to thecourt. Therefore, it needs to be studied in this study. The findings in this study are . Therights and obligations of the parties must be protected by law. Arbitration and BANI rulesand procedures.Keywords: Legal Protection, Construction, Abitrase